Implementasi Pendidikan Karakter dan Moderasi Beragama di MTs Qurrota A’yun Yogyakarta - Muhammad Rasyid RIdho; Muhammad Wasith Achdi (Lembaga Yasin AlSys, 2026)
The rapid development of globalization and the flow of digitalization have had a significant impact on the behavior of the young generation, including in madrasah tsanawiyah settings, as reflected in declining morality, weakening social concern, and strengthening individualism. This study aimed to analyze the implementation of character education and religious moderation at MTs Qurrota A’yun Yogyakarta as a strategy for fostering students’ moral and spiritual development in the digital era. A qualitative approach with a case study design was employed, using observation, in-depth interviews, and documentation as data collection techniques, and interactive analysis based on Creswell’s model. The findings show that character education and religious moderation programs are integrated into the curriculum, intra-curricular and extracurricular activities such as mabit, Pramuka, and tauhid studies, as well as madrasah culture grounded in role modeling and the habituation of religious, disciplined, responsible, and tolerant values. Program evaluation is carried out reflectively and continuously through collaboration among teachers, students, and parents. The study indicates that the implementation of these programs not only enhances students’ spirituality and social character, but also strengthens a culture of religious moderation and offers a model of Islamic education that is adaptive, humanistic, and contextually responsive to the challenges of globalization and digitalization.